Thermodynamic properties of the liquid Ag-Bi-Cu-Sn lead-free solder alloys - Garzel G.; Kopyto M.; Zabdyr L.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The electromotive force measurement method was employed to determine the thermodynamic properties of liquid Ag-Bi-Cu-Sn alloys using solid electrolyte galvanic cells as shown below: Kanthal+Re, Ag-Bi-Cu-Sn, SnO2 | Yttria Stabilized Zirconia | air, Pt, Experiments were made within temperature interval: 950 - 1300K along four composition paths of constant ratios: XAg : XBi : XCu = 1, XAg : (XBi + XCu) = 3:2 for XBi = XCu, XBi : (XAg + XCu) = 3:2 for XAg = XCu and XCu : (XAg + XBi) = 3:2 for XAg = XBi and tin concentration changing from 0.1 to 0.9 mole fractions, every 0.1. Almost all the results were approximated by straight line equations: EMF vs T, and tin activities were then calculated in arbitrary temperature; measurement results were presented by graphs. Unusual activity plot for XBi : (XAg + XCu) = 3:2 composition path was most probably caused by miscibility gap detected earlier in Bi-Cu-Sn ternary liquid alloys.